2021
DOI: 10.1111/1756-185x.14269
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the 2019 European League Against Rheumatism/American College of Rheumatology classification criteria for systemic lupus erythematosus in a multiethnic Malaysian cohort

Abstract: Aim To evaluate the performance of the 2019 European League Against Rheumatism/American College of Rheumatology (EULAR/ACR) classification criteria for systemic lupus erythematosus (SLE) in a multi‐ethnic Malaysian cohort and to compare it against the Systemic Lupus International Collaborating Clinics (SLICC) 2012 and ACR 1997 criteria. Method We conducted a retrospective observational study of 205 patients with a diagnosis of SLE and 100 controls who formed the validation cohort. The sensitivity and specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 40 publications
1
19
0
3
Order By: Relevance
“…12 A Malaysian study published recently reported that the sensitivity of EULAR/ACR-2019 classification standard was 91% and the specificity was 94%. 15 In the present study, EULAR/ drug accuracy of 97.4%, 91.4%, According to the results of our study, the AUCs (95% CI) of ACR-1997, SLICC-2012 and EULAR/ACR-2019 were 0.972 (0.962 to 0.982), 0.986 (0.979 to 0.993) and 0.983 (0.973 to 0.992), respectively. This proved that the diagnostic results of the three sets of classification criteria were highly similar to the results of clinical diagnosis (the gold standard adopted in our study).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…12 A Malaysian study published recently reported that the sensitivity of EULAR/ACR-2019 classification standard was 91% and the specificity was 94%. 15 In the present study, EULAR/ drug accuracy of 97.4%, 91.4%, According to the results of our study, the AUCs (95% CI) of ACR-1997, SLICC-2012 and EULAR/ACR-2019 were 0.972 (0.962 to 0.982), 0.986 (0.979 to 0.993) and 0.983 (0.973 to 0.992), respectively. This proved that the diagnostic results of the three sets of classification criteria were highly similar to the results of clinical diagnosis (the gold standard adopted in our study).…”
Section: Discussionsupporting
confidence: 71%
“…The sensitivity of ACR-1997, SLICC-2012 and EULAR/ACR-2019 was 86%, 98%, and 94%, respectively; and the sensitivity of SLICC-2012 was significantly higher than that of ACR-1997. 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical manifestations of SLE are heterogeneous, involving the blood, kidney, nerve and some other systems, making the treatment and management difficult and complicated (2). Currently, the Chinese hospitals often adopt European and American (EULAR/ACR) diagnostic guidelines for SLE diagnosis (3,4), whereas the molecular profiling of SLE is highly heterogeneous among different races and locations (5,6). Consequently, the specificity and sensitivity of diagnostic indicators recommended by the EULAR/ACR need to be validated further in Chinese population.…”
Section: Introductionmentioning
confidence: 99%